An Improved Passing Network for Evaluating Football Team Performance - Wenxuan Zhou; Guo Yu; Songhui You; Zejun Wang (Applied Sciences, 2023)
With the continuous development of sensor technology, the realization of football techniques and tactics comes with richer technical support. Among them, network analysis has been widely used to analyze passing behavior, and some results have been achieved. However, most of these studies directly determine the weight of passing sidelines between players by measuring the number of passes, without carefully considering the potential contribution value of a single pass. In view of this problem, we carried out the following work: (1) map the football field to the coordinate system, calculate the endpoint coordinates of each pass, and take the coordinates as coefficients to obtain the weighted value of a single channel, and then calculate all channels together to achieve a directional channel network. (2) On this network, for the team evaluation that is difficult to quantify, we suggest that the ratio of the average clustering coefficient to the average intermediate centrality be taken as the overall network index to measure the coordination of the football team’s performance. (3) We tested the proposed index with two scores. The index passed the correlation and sensitivity tests, which proves that it is helpful for explaining the coordination level of the team and has certain reference value for the evaluation of the competitiveness of the football team.